THE EFFECTIVENESS OF INTEGRATED LEARNING MODEL TO IMPROVE THE STUDENTS COMPETENCE AT ELEMENTARY SCHOOL - Amini, Risda; Lena, Mai Sri (Department of Integrated Science, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang in Collaboration with Perkumpulan Pendidikan IPA Indonesia, 2019)
The demand of curriculum in 2006, learning in elementary school is implemented a thematically so that students are able to think critically, creatively, and have a scientific character. Preliminary surveys indicated that the problems by elementary school teachers was difficult to conduct the thematic learning, so that students were less active. Many students who had difficulty in learning and answering questions in textbooks that have been available online. There were still many students who have not mastered learning. The low competence of the students was the caused by several problems, the learning is not fun, not interesting, and yet challenging for the students, so the students find it difficult to learn the theme in the textbooks. Teachers have not used the method of learning in accordance with the theme and facilities supporting the learning process. One way to facilitate students in learning is through integrated learning models. This research aims to determine the effectiveness of the integrated learning model for improving the students’ competence. The research used a quasi-experimental method with pretest-posttest group control design. Subjects of this research were third grade students at elementary school (SDN 64) in Payakumbuh. Data were collected using observation sheets, the achievement test, skills assessment sheets, questionnaires. The results showed that integrated learning model was effective to improving the students’ competence, in terms of (1) the mastery of learning had been achieved by most students, (2) there was an improvement of students' competence, (3) average of students’ learning outcomes of experiment class was higher than control class, (4) the average of students skills in conducting experiment were good.